The Association Between School Start Time and Sleep Duration, Sustained Attention, and Academic Performance - Alfonsi V (Dove Medical Press, 2020)
Valentina Alfonsi,1,2 Rossella Palmizio,3 Annalisa Rubino,3 Serena Scarpelli,2 Maurizio Gorgoni,1 Aurora D’Atri,4 Mariella Pazzaglia,1,2 Michele Ferrara,4 Salvatore Giuliano,3 Luigi De Gennaro1,2 1Department of Psychology, “Sapienza” University of Rome, Rome, Italy; 2I.R.C.C.S. Fondazione Santa Lucia, Rome, Italy; 3I.I.S.S. “Ettore Majorana”, Brindisi, Italy; 4Department of Biotechnological and Applied Clinical Sciences, University of L’Aquila, L’Aquila, ItalyCorrespondence: Luigi De Gennaro“Sapienza” University of Rome, Via Dei Marsi, 78, Rome 00185, ItalyTel (+39) 06-49917647Fax (+39) 06-49917711Email luigi.degennaro@uniroma1.itPurpose: In adolescence, physiological (circadian and homeostatic regulation of sleep) and social habits contribute to delayed sleep onset, while social obligations impose early sleep offset. The effects of delayed school start time on the subjective/objective measures of sleep–wake patterns and academic achievement have not been established.Methods: This pre-, post-, and longitudinal non-randomized study included an early (8:00 am; ESC=30 students) and the late (9:00 am; LSC=21 students) start class. Multiple sleep data included a weekly sleep diary, Karolinska Sleepiness Scale, Pittsburgh Sleep Quality Index, and Epworth Sleepiness Scale. Sustained attention was measured using the Psychomotor Vigilance Task. Academic performance was evaluated by two different mathematical and scientific standard tests (entrance and final) and by school attendance indicators. Data were collected at monthly intervals from October 2018 to May 2019 and the beginning and end of the academic year (pre/post).Results: All students turned their lights off at similar times (LSC=11:21pm, ESC=11:11pm), but LSC students woke up later (7:23am) than ESC students (6:55am; F1,48=11.81, p=0.001) on school days. The groups did not differ in total sleep duration on non-school days. Longitudinal measures revealed a significant increase (8.9%, 34 min) in total sleep duration of LSC students across the academic year. ESC students maintained approximately the same sleep duration. Furthermore, changes in sleep duration had parallelled significant differences in sustained attention, with LSC students outperforming ESC students. Longitudinal changes of sleep and sustained attention were associated with a coherent pattern of changes in academic performance.Conclusion: Findings indicate that a one-hour delay in school start time is associated with longer sleep, better diurnal sustained attention, attendance, and improved academic performance. Notably, sleep changes were limited to school days. A delay in school start time should be seriously considered to improve sleep and academic achievements of students.Keywords: sleep, school start time, attention, school health, sleep loss, adolescence